An Analysis of the Main Character Conflict of the Roommate Movie Script by Sonny Malhi - Mukhlas, Mukhlas; Asyari, Ahmad Khasan; Hidayah, Nurul; Kirom, Siti Masirotul; Pratama, Risky (Siliwangi University, 2023)
This study provides a comprehensive examination of the primary character conflict in the movie script